Effects of Prebiotics, Probiotics, and Synbiotics on the Bodyweight, Blood Glucose, Triglyceride and TNF-α of Diet-induced Obesity Rats - Lenny Octavia; Soebagijo Adi Soelistijo; Agung Dwi Wahyu Widodo (Universitas Muhammadiyah Surabaya, 2020)
Abstract High-fat diet leads to obesity-associated chronic low-grade inflammation. Prebiotics, probiotics, and synbiotics produced short-chain fatty acids (SCFA), bonded to G protein-coupled receptors (GPR)-41 and GPR-43 decreased triglyceride deposits in adipocytes and liver, decreased fatty acid oxidation, increased glucose regulation and insulin sensitivity thus reduced the risk of obesity and metabolic syndrome. This study conducted in order to evaluate the effects of prebiotics, probiotics, and synbiotics on the body weight, blood glucose, triglyceride, and TNF-α used rats model, which were fed by a high-fat diet. Thirty-eight 6-8 weeks old male rats were fed by high-fat diet for three weeks, then rats were randomly divided into four groups, high-fat diet (HFD), a high fat diet with prebiotics supplementation (HFD+ PRE), a high fat diet with probiotics supplementation (HFD+PRO), and high-fat diet with synbiotics supplementation (HFD+SYN) for three weeks. Blood samples and body weight were measured at the third and sixth week. There was no effect of prebiotics, probiotics, and synbiotics on body weight, triglyceride levels, blood glucose, and TNF-α in rats fed a high-fat diet compared to control. These results suggested that supplementations gave inconsistent results with other studies and needed further researches.Keywords : high fat diet, prebiotics, probiotics, synbiotics, meta-inflammationCorrespondence : soebagijo@yahoo.com